Recent Surgical Methods of Double-door Laminoplasty of the Cervical Spine (Kurokawa's Method) - Hirabayashi, Shigeru (Spine Surg Relat Res, 2018)
INTRODUCTION: Double-door laminoplasty (DDL) of the cervical spine (Kurokawa's method) was developed as one of posterior decompression surgical methods in the late 1970s and after then has been modified by adding various procedures such as the posterior muscle handling and the use of artificial spacers. There are three principles of DDL: First, to decompress the cervical spinal cord by central splitting of the spinous processes and laminae, preserving those lengths as much as possible and widening the spinal canal space symmetrically. Second, to maintain the widened spinal canal space steadily by fixing spacers made of hydroxyapatite the contour is almost the same as the widened space. Third, to re-suture the semispinalis muscles to the C2 spinous process to restore the strength of the posterior cervical muscles. TECHNICAL NOTE: The important technical points in performing osteotomy are as follows: At each vertebra, osteotomy is performed from the caudal side and gradually proceeds to the cranial side because there is a space between the lamina and the dura mater at the caudal side and the osteotomy can be safely made. The surgeon must pay attention to the changes in color of the osteotomy site from red of cancellous bone, to white of the inner cortex, and finally to yellow of the yellow ligament and extradural fat tissue. Attention must be paid to the changes in sound and tactile sensation delivered from the air-drill when completing osteotomy of the inner cortex of lamina. By moving an air-drill slowly, tactile sensation can be more sensitive. During osteotomy, the process must be checked frequently by touching the inner cortex of the lamina with a probe. CONCLUSION: At present, DDL is a useful surgical method for cervical myelopathy at multiple level lesions.